Influence of dietary selenium and vitamin E on the levels of fatty acids in brain and liver tissues of lambs - Çelik, S; Yilmaz, Ö; Asan, T; Naziroglu, M; Çay, M; Aksakal, M (John Wiley & Sons Ltd, 1999)
In this study, the effects of dietary vitamin E, selenium, and their combination on the levels of fatty acid composition of the brain and liver tissues were examined. In brain tissue, the amounts of most fatty acids increased in vitamin E, combination and selenium groups compared with control group values. While the proportions of myristic, pentadecanoic, palmitic, linoleic, and total saturated fatty acids were decreased in vitamin E, Se and combination groups, eicosapentaenoic, total unsaturated and MUFA were increased in the same groups. In addition, the proportions arachidonic. eicosapentaenoic, total unsaturated, omega 6 and MUFA in the combination group were higher than in the control group. In liver tissue, the amounts of myristic, pentadecanoic, palmitic, eicosedienoic, eicosapentaenoic, docosahexaenoic, omega 3 and PUFA were higher in the combination group than in the control group. Also the proportions of eicosapentaenoic, docosahexaenoic acids in supplemented groups were higher than those in the control group. We conclude that dietary vitamin E and selenium have an influence on the levels of fatty acids in the brain and liver. Copyright (C) 1999 John Wiley & Sons, Ltd.
Keywords: dietary selenium and vitamin E; brain; liver; fatty acids